Exploring the Relationship Between Deficits in Social Cognition and Neurodegenerative Dementia: A Systematic Review - Setién-Suero, Esther; Murillo-García, Nancy; Sevilla-Ramos, Manuel; Abreu-Fernández, Georgelina; Pozueta, Ana; Ayesa-Arriola, Rosa (Frontiers in Aging Neuroscience, 2022)
Background: Neurodegenerative diseases might affect social cognition in various ways depending on their components (theory of mind, emotional processing, attribution bias and social perception) and the subtype of dementia they cause. This review aims to explore this difference in cognitive function among individuals with different aetiologies of dementia. Methods: The following databases were explored: MEDLINE via PubMed, Cochrane Library, Lilacs, Web of Science and PsycINFO. We selected studies examining social cognition in individuals with neurodegenerative diseases in which dementia was the primary symptom that was studied. The neurodegenerative diseases included Alzheimer’s disease, Lewy body disease and frontotemporal lobar degeneration. The search yielded 2803 articles. Results: One hundred twenty-two articles were included in the present review. The summarized results indicate that people with neurodegenerative diseases indeed have deficits in social cognitive performance. Specifically, in populations with Alzheimer’s disease, the domain that was most strongly affected was emotional processing, while in populations with frontotemporal dementia, a similar deterioration in emotional processing and theory of mind was observed. The data indicate that deterioration occurs in a distinct manner depending on the type of neurodegenerative disease and the social cognitive domain being analysed. Conclusions: Each type of dementia has a differential profile of social cognition deterioration. This review could provide a useful reference for clinicians to improve detection and diagnosis, which would undoubtedly guarantee better interventions.